Demencia rápidamente progresiva por meningitis criptocócica: Reporte de caso - Annelise Velasco de Azevedo-Pereira (Asociación Colombiana de Infectología, 2022)
Dementias constitute a group of degenerative diseases that affect different domains within human cognition. While the usual course is chronically progressive, a small group of patients develops a subacute deterioration in months, an entity that is called rapidly progressive dementia. For these patients, an approach based on considering reversible etiologies is mandatory, and its diagnosis must be taken into consideration not only in immunocompromised patients by the human immunodeficiency virus (HIV) but also in patients with other causes of immunosuppression. We report the case of a patient with chronic use of steroids that developed rapidly progressive dementia as the sole manifestation of cryptococcal meningoencephalitis.